GAMBARAN TINGKAT STRES LANSIA PADA MASA PANDEMI CORONA VIRUS DISEASE-19 - Putu Adi Cahya Dewi (JURNAL MEDIKA USADA, 2022)
Introduction: The elderly are one of the vulnerable groups who have high morbidity and mortality during the COVID-19 pandemic. The elderly had a physical problems and psychological during pandemi such as anxietas, stress and depression abaut COVID-19. The purpose of this study was to describe the stress level of the elderly during the COVID-19 pandemic in Banjar Delod Bale Agung, Mengwi Village, Working Area of ​​UPT Puskesmas Mengwi I. Methods: The research method used was descriptive research with a cross sectional approach. The research sample amounted to 134 elderly people who live or settle in Banjar Delod Bale Agung, Mengwi Village, with a simple random sampling technique. Data were collected by questionnaire and analyzed by descriptive statistical test. Results: The results of the study were obtained from 134 respondents with stress levels in the elderly during the COVID-19 pandemic, namely moderate stress (35.1%), no stress (25.4%), severe stress (21.6%) and mild stress (17). ,9%). Discussion: The majority of the elderly experience moderate stress during the COVID-19 pandemic which can affect the health of the elderly, so it is very important to improve the assistance of the elderly and provide support from both families and nurse.